Actuators Fault Diagnosis and Tolerant Control for an Unmanned Aerial Vehicle - Bateman, F.; Noura, H.; Ouladsine, M. (2007 IEEE International Conference on Control Applications, 2007)
In this paper a fault detection and isolation (FDI) method coupled with a fault tolerant control system are developed in order to deal with control surface failures for an Unmanned Aerial Vehicle (UAV). The failures considered are stuck control surfaces which occur during the aircraft manoeuvres: turn, velocity and slope variations. These faults are difficult to detect and to isolate. On the one hand they are soft variations and the aircraft is equipped with a controller which mask them, on the other hand redundancies offered by the control surfaces cause problems of isolability. The Fault Detection and Isolation system proposed here is based on a signal processing approach and drives a Fault Tolerant Control System (FTCS) built with a bank of Linear Quadratic controllers.